Targeting KRASG12V mutations with HLA class II-restricted TCR for the immunotherapy in solid tumors - Ai, Qi; Li, Fanlu; Zou, Siyi; Zhang, Zehui; Jin, Yangbing; Jiang, Lingxi; Chen, Hao; Deng, Xiaxing; Peng, Chenghong; Mou, Nan; Wen, Chenlei; Shen, Baiyong; et al. (Frontiers in Immunology, 2023)
KRAS mutation is a significant driving factor of tumor, and KRASG12V mutation has the highest incidence in solid tumors such as pancreatic cancer and colorectal cancer. Thus, KRASG12V neoantigen-specific TCR-engineered T cells could be a promising cancer treatment approach for pancreatic cancer. Previous studies had reported that KRASG12V-reactive TCRs originated from patients’ TILs could recognized KRASG12V neoantigen presented by specific HLA subtypes and remove tumor persistently in vitro and in vivo. However, TCR drugs are different from antibody drugs in that they are HLA-restricted. The different ethnic distribution of HLA greatly limits the applicability of TCR drugs in Chinese population. In this study, we have identified a KRASG12V-specific TCR which recognized class Ⅱ MHC from a colorectal cancer patient. Interestingly, we observed that KRASG12V-specific TCR-engineered CD4+ T cells, not CD8+ T cells, demonstrated significant efficacy in vitro and in xenograft mouse model, exhibiting stable expression and targeting specificity of TCR when co-cultured with APCs presenting KRASG12V peptides. TCR-engineered CD4+ T cells were co-cultured with APCs loaded with neoantigen, and then HLA subtypes were identified by the secretion of IFN-γ. Collectively, our data suggest that TCR-engineered CD4+ T cells can be used to target KRASG12V mutation presented by HLA-DPB1*03:01 and DPB1*14:01, which provide a high population coverage and are more suitable for the clinical transformation for Chinese, and mediate tumor killing effect like CD8+ T cells. This TCR hold promise for precision therapy in immunotherapy of solid tumors as an attractive candidate.